Sildenafil for pulmonary hypertension due to left-toright shunt after corrective procedure - Dyahris Kuntartiwi; Piprim Basarah Yanuarso; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2015)
Background Pulmonary arterial hypertension (PAH) is a common complication seen in those with a left-to-right shunt congenital heart defect (CHD). Corrective procedures by surgery or catheterization are the therapies of choice for reversible PAH. Since morbidity and mortality due to PAH after correction is high, sildenafil has been used as a selective vasodilator of the pulmonary artery, in order to decrease pulmonary arterial pressure. Objectives To evaluate the effect of sildenafil on pulmonary arterial pressure and clinical outcomes after left-to-right shunt CHD corrective procedures. Methods Left-to-right shunt patients aged < 18 years scheduled for corrective treatment were randomized in a double-blind fashion, to receive either oral sildenafil or placebo, given on days 3 to 30 after the corrective procedure. Clinical and pulmonary arterial pressures were evaluated by echocardiography before, 3 days after, and 30 days after the corrective procedure. Results From July 2013 to June 2014, 36 patients were included in the study: 17 in the placebo and 19 in the sildenafil groups. There were no differences in pulmonary arterial pressure or in clinical outcomes after corrective procedure between the two groups. There were no adverse events during the treatment. Conclusion Sildenafil has little effect on decreasing pulmonary arterial pressure, as most of our subjects seem to have hyperkinetic PAH. As such, pulmonary arterial pressure returns to normal soon after corrective procedures.